MAKING AND CHARACTERIZATION OF CORN STARCH-BASED BIOPLASTIC AND STUDY ABOUT BIODEGRADABILITY OF BIOPLASTICS - Fauzan Bagaskoro, Ahmad
This report concerns with the study of biodegradability of bioplastics and the characteristics of bioplastic samples that was made using corn starch. Biodegradability of bioplastics was studied via literature review. Generally, bioplastics have better level of biodegradability compared to that of conventional plastics. There are some factors influencing the level of biodegradability of bioplastics, i.e. the type of microorganism, media selection, and additional substances at bioplastics. A bioplastic sample was made using corn starch, aquadest, glycerol, and acetic acid. The bioplastic was then characterized through tensile testing and TG/DTA (thermogravimetric/differential thermal analysis) characterization. It was found that the modulus of elasticity and Hookean constants are ????=(269.430,1299±89.555,2949) MPa and ????=(4.648.984.426,1646±2.460.336.885,2044) N/m, respectively. From TG/DTA analysis, it was found that the made bioplastic relatively stable at 100-200°C and started to degrade significantly at 300°C.